Access audit for persons with disabilities at local authority buildings / Mohamad Faiz Mohamad - Mohamad, Mohamad Faiz (Faculty of Architecture, Planning and Surveying, 2010)
The local authority is an organization that governs the small region in state government. The local authority building is the center of municipal, towns or cities where it receives a visit from any kind of people - young or old, short or tall, normal or disabled people for several of business Local authority should be ready and provide the best and excellent facilities to receive a visit from its clients especially person with disabilities to access into this building. It should prepare the safe and comfort facilities and the facilities should in good and safe conditions. This study is to make sure the person with disability facilities provided by local authority buildings are follow the Malaysian Standard code of practice of access for disabled peoples to public buildings and outside the buildings MS 1331 and MS 1184. All the information that gathered from study case is analyzed. The appropriate solution and recommendation are identified to solve the existing problems. The study also may be used as a future references for future studies.